"You are not alone": Connecting through a bereaved parent mentor program for parents whose child died of cancer. (1st April 2022) - McNeil, Michael J.; Kiefer, Ashley; Woods, Cameka; Barnett, Brittany; Berry‐Carter, Kathryn; Clark, Lisa; Mandrell, Belinda N.; Snaman, Jennifer; Kaye, Erica C.; Baker, Justin N.
Abstract: Background: Bereavement after the death of a child is devastating and associated with worse physical and psychosocial well‐being in parents. Evidence suggests that parents desire and benefit from support provided by other bereaved parents. To foster this peer support, an institutional peer‐to‐peer mentorship program for bereaved parents was established, through which trained bereaved parent mentors offer support for newly bereaved parents. Methods: Using a retrospective cohort design, we describe the characteristics of participants of the Bereaved Parent Mentorship program. Trained bereaved parent mentors documented encounters with newly bereaved parent mentees using a secure internet‐based form. Mentors summarized each encounter including any concerns or need for professional psychosocial support. Descriptive statistics were used to describe mentor and mentee characteristics; free text from encounter summaries was qualitatively analyzed using content analysis. Results: A total of 1368 documented encounters occurred between 150 mentees and 39 mentors from January 1, 2014 to February 29, 2020. Only seven encounters (0.5%) were flagged as serious concern necessitating professional psychosocial support. Four key themes in the encounters between mentors and mentees emerged, including: descriptions of the grief experience, ways in which a mentor supported their mentee, challenges the mentor experienced in supporting the mentee, and personal benefit gained by the mentor from supporting their mentee. Conclusion: This structured Bereaved Parent Mentorship program fostered rich interactions between bereaved parent participants, with very few encounters requiring professional assistance. Future research will assess the impact of bereaved mentor programs on resilience and psychosocial, physical, and functional well‐being of parents. Abstract : This structured Bereaved Parent Mentorship program for parents whose children died of cancer fostered rich interactions between bereaved parent participants. Very few encounters in this program required professional psychosocial assistance. Future research will assess the impact of bereaved mentor programs on resilience and psychosocial, physical, and functional well‐being of parents.